Suicidal attempt with high dose long-acting methylphenidate: A case report - (:unkn) unknown (My University, 2013)
Stimülanlar, dikkat eksikliği hiperaktivite bozukluğu (DEHBtedavisinde yaygın olarak kullanılan ilaçlardır. Literatürde, DEHB olgularında uzun etkili metilfenidat ile intihar girişimi olgu sunumları sınırlı sayıdadır. Bu olgu sunumunda 1350 mg uzun etkili metilfenidat ve 2 mg risperidon ile intihar girişiminde bulunan 13 yaşında erkek hasta tartışılmıştır. Hastada hayatı tehdit eden belirtiler olmamakla birlikte acil tıbbi müdahale gerekli olmuştur.

Stimulant medications are the most commonly used drugs for the treatment of attention-deficit hyperactivity disorder (ADHD). Reports of suicide attempts in ADHD cases with high dose long- acting methylphenidate (MPH) are limited in the literature. In this case report, a 13-year-old boy who had attempted suicide by ingesting 1350 mg long-acting MPH and 2 mg risperidon is discussed. While the patient did not have life threatening symptoms, emergency medical intervention was necessary.
Yüksek doz metilfenidat ile intihar girişimi: Bir olgu sunumu
Keywords: Genel ve Dahili Tıp